Model on Problem Characteristics and Sustainable Development of Rural Tourism in Guangdong Province Based on Type Attribute. Issue 1 (February 2020) - Wang, Ning; Du, Changchun
Abstract: The 19th National Congress of the Communist Party of China stressed the new urbanization strategies, pointing out the promotion of the development from traditional urbanization to new urbanization, which contains the development characteristics as urban and rural overall development, industry interaction, economical and intensive land and harmonious development. It aims to solve the issues relating to agriculture, farmers and rural areas with the strategy of rural vitalization which takes rural tourism as the starting point to drive the development of rural economy, and then realizes the new urbanization. The purpose of this paper is to study the problem characteristics and corresponding classification of rural tourism in Guangdong and establish the sustainable development model of rural tourism in Guangdong. This paper starts from the perspective of rural revitalization, takes the new urbanization as the background, combines the theoretical basis and the realistic environmental factors, extracts the development appeals, existing main problems and causes of rural tourism in Guangdong, and classifies them by combining the characteristics of resource types and other factors. On this basis, combining with the successful experience of rural development at home and abroad, this paper puts forward the selection of the pedigree of sustainable development mode of rural tourism in Guangdong, and the differentiated and targeted design responding to control countermeasures and safeguard mechanism of sustainable development of rural tourism in Guangdong in the context of new urbanization. The experimental results show that the establishment of the sustainable development model of rural tourism can effectively alleviate the existing problems in rural tourism, promote the development of new urbanization and realize the strategy of rural revitalization.